Maria Petyt : a Carmelite mystic in wartime - Chalmers, Joseph; Hense, Elisabeth; Meeuwsen, Veronie; Vate, Esther van de (Radboud studies in humanities, 2015)
Based on the discovery of an unknown Latin manuscript, 'Maria Petyt - A Carmelite Mystic in Wartime' provides surprising new information about the seventeenth century Flemish mystic Maria Petyt (1623-1677) who wrote many letters to her spiritual director, Michael of St. Augustine. The book contains a transcription of the (unfortunately partly damaged) manuscript, an English translation of it, and several articles opening up new horizons concerning the life and spirituality of Maria Petyt and her historical and religious backgrounds. The authors characterize Maria Petyt as a self-confident spiritual daughter with a strong political mission, a zealous figure fighting side by side with Louis XIV for the catholic victory during the Dutch War, and as one who lived and profoundly understood the spirituality of Teresa of Avila.